An assessment of the monkfish resource of Namibia - Maartens, Lima (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2000)
Two monkfish species are caught off the coast of Namibia. These are Lophius vomerinus Valenciennes (1837) and L. vaillanti Regan (1903). L. vomerinus is the more abundant of the two and contributes approximately 99% to the total Namibian monkfish landings. The Namibian monkfish fishery is one of the largest and most valuable of its kind in the world. Two fishing fleets harvest the resource, viz. the monkfish and sole fleet and the hake directed fleet. In 1998 and 1999, monkfish were also harvested by one gillnet vessel that had an experimental right. In this study, the biology, abundance and exploitation patterns of monkfish were investigated and used as inputs into a stock assessment framework as a contribution towards the development of a management procedure for this species. Ground and sectioned otoliths and sectioned illicia were used to age Lophius vomerinus. The illicia provided more precise estimates of age, and growth was subsequently modelled using these age estimates. Growth in length and weight was best described by the threeparameter specialised von Bertalanffy model as Lt (cm TL) = 72.29 (1-eâ »Â°Â·Â¹â ´â ½tâ ºÂ°Â·Â³Â°â ¾) and Wt (kg) = 3.96 (1-eâ »Â°Â·Â¹â ¸â ½tâ ºÂ°Â·Â¹Â°â ¾)Â²Â·â ¹â ¹ for males, and Lt (cm TL) = 111.98 (1-eâ »Â°Â·Â°â ¸â ½tâ ºÂ°Â·Â³â ¶â ¾) and Wt (kg) = 6.92 (1-eâ »Â°Â·Â¹â ¸â ½tâ »Â°Â·â ¶â ´â ¾)Â³Â·Â°Â³ for females. L. vomerinus is a slow-growing species with a life span in excess of 10 years. Reproductive activity was shown to occur throughout the year, with a slight peak during the winter months. The adult sex ratio of fish > 37 cm TL was biased towards females. Length-at-50% sexual maturity was attained at 32.1 cm TL for females and 23.7 cm TL for males. The rate of natural mortality was estimated at 0.15 yearâ »Â¹, while fishing mortality rates during the 1970s, 1980s and 1990s were estimated at 0.01 yearâ »Â¹, 0.04 yearâ »Â¹ and 0.14 yearâ »Â¹, respectively. Gillnetting for monkfish (300 mm stretched mesh) was highly efficient with a moderate bycatch of around 20% during the two years of operation. The main bycatch species were red crab, spider crab, squalid sharks, rays and Cape and Deep-water hake. The mean length of the monkfish caught in gillnets (67 cm TL) was significantly larger than the monkfish landed by the trawlers (38 cm TL) and less than 1% of immature fish were landed. Gillnet catch-per-unit-effort for monkfish fluctuated between 0.03 and 0.67 kg.dayâ »Â¹.50 m net panelâ »Â¹, with a soak time of between one and sixteen days. More than 50% (by weight) of monkfish landed by monkfish and sole trawlers, consisted of fish below 36 cm TL. There was a significant increase in catches of juvenile monkfish during 1997 and 1998 in comparison to the period 1994 to 1996. Various types of rigid sorting grids were tested to release juvenile monkfish below 32 cm TL. Five grid designs were tested. These included an "Ex-it" grid with horizontal bars spaced at 55 mm, single grids with vertical and horizontal bars spaced at 55 mm and grids with circular openings of 110 and 168 mm in diameter. The most efficient design was the grid with circular openings of 110 cm in diameter, which ensured the escape of 66% of monkfish smaller than 31 cm TL. However, studies need to be undertaken to quantify the survival of released fish and to test the feasibility of using grid sorters on commercial monkfish and sole trawling gear. The monkfish resource was assessed by means of length cohort analyses, the Thompson and Bell predictive model and by way of a deterministic age-structured production modelling approach. The length cohort analysis models were sensitive to the rate of natural mortality and insensitive to changes in the terminal fishing mortality rate. These biases may, however, not be serious provided that estimates of abundance are used to reflect relative changes. Fish ranging between 26 and 59 cm TL are the most heavily exploited. The Thompson and Bell model predicted that the monkfish resource is exploited above MSY -levels and a reduction of approximately 40% in fishing effort would provide a higher yield. Yield-per-recruit ranged between 10 000 and 14 000 tonnes. Results should, however, be treated with caution, as the condition of steady state was not satisfied. The age-structured production model was tuned using trends in catch-per-unit-effort data, estimated by Generalised Linear Modeling, as well as relative abundance indices calculated from hake biomass surveys. The model was found to be sensitive to both the 'steepness' parameter h and estimates of natural mortality. The 'depletion' level of the monkfish resource is currently estimated to be 49%. Estimated coefficients of variation were high (> 63%) due to the lack of a consistent trend within the abundance indices to tune the model. Overall productivity of the monkfish resource was estimated to be approximately 16%, similar to other southern African demersal resources. Results of the risk analyses suggest that catches in excess of 7 000 tonnes may be unsustainable and that catches of 5 000 or 6 000 tonnes would decrease the risk of stock collapse and possibly lead to a recovery in the stock. Monkfish management strategies were reviewed and these were considered in relation to the results of this study. The following management recommendations were made: to follow the precautionary approach and implement a total allowable catch for monkfish; to implement rigid sorting grids as these would be the most appropriate way in which to reduce catches of juvenile monkfish; to restrict soak time, depth of operation and implement means to reduce 'ghost fishing' by gillnetting and finally, to develop a management procedure for Namibian monkfish with the main objective being the sustainable exploitation of the resource.
Keywords: Lophius -- Namibia; Lophius